1993
DOI: 10.1152/jappl.1993.74.5.2099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dynamic exercise on renal sympathetic nerve activity in conscious rabbits

Abstract: Renal sympathetic nerve activity (RSNA) increases abruptly at the onset of treadmill exercise in conscious rabbits. This study investigated whether the rise in RSNA is related to the intensity of the exercise and whether an elevated level of RSNA is maintained during submaximal exercise. RSNA, arterial blood pressure (BP), and heart rate (HR) were recorded in 10 New Zealand White rabbits during two treadmill exercise protocols at 0% grade: 7 m/min for 5 min and 12 m/min for 2 min. Peak levels of RSNA were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…This study, which was performed on conscious rabbits, demonstrated that renal vasoconstriction was increased within 10 s of initiation of dynamic exercise in the innervated kidney, whereas no such response was seen in the denervated kidney. Other studies on cats and rabbits have also found that renal sympathetic nerve activity increases within seconds after the onset of muscle contraction (11,15,18).…”
Section: Protocol 2: Static Handgrip Exercise At Graded Intensitymentioning
confidence: 84%
“…This study, which was performed on conscious rabbits, demonstrated that renal vasoconstriction was increased within 10 s of initiation of dynamic exercise in the innervated kidney, whereas no such response was seen in the denervated kidney. Other studies on cats and rabbits have also found that renal sympathetic nerve activity increases within seconds after the onset of muscle contraction (11,15,18).…”
Section: Protocol 2: Static Handgrip Exercise At Graded Intensitymentioning
confidence: 84%
“…These findings are consistent with work in cats in which pharmacological blockade of skeletal muscle stretch activated ion channels did not influence early increases in BP during spontaneous muscle contractions (i.e., central command induced pressor response) (201). However, the autonomic contribution to potential central command induced early increases in BP has yet to be fully determined, although in support of a sympathetic contribution, BP and renal SNA have been shown to increase prior to and at the onset of static exercise (206), locomotion (277), grooming (203) and treadmill exercise (237) in animals. Although not specifically designed to examine the onset of exercise, work from Victor and colleagues using brief rhythmic handgrip exercise and partial neuromuscular blockade lends some additional insight (355).…”
Section: Central Command At Exercise Onsetmentioning
confidence: 99%
“…The increase in skin SNA at exercise onset appears proportional to the exercise intensity and remains elevated throughout exercise (267,283,344,358,359). Likewise, animal investigations demonstrated immediate increases in renal and cardiac SNA at the onset of dynamic exercise (54,237,346). Overall, the onset of dynamic exercise does not appear to produce mass, uniform sympathetic discharge to all tissues, rather the majority of studies suggest selective sympathetic activation at exercise onset.…”
Section: Peripheral Sympathetic Activity At Exercise Onsetmentioning
confidence: 99%
“…Cardiac, renal, and lumbar sympathetic nerve activities also demonstrate a rapid increase at the beginning of dynamic exercise or natural body movement in cats (13,20,22,30,48), rabbits (37), and rats (6). Central command is the most likely to cause the prompt sympathoexcitation, which in turn contributes to the cardiovascular adaptation at the beginning of static or dynamic exercise.…”
mentioning
confidence: 97%